2020
DOI: 10.2147/opth.s271569
|View full text |Cite
|
Sign up to set email alerts
|

<p>Conjunctival Melanoma: Update on Genetics, Epigenetics and Targeted Molecular and Immune-Based Therapies</p>

Abstract: Purpose: To present the molecular mechanisms involved in the pathogenesis of conjunctival melanoma (CM) and review the existing literature on targeted molecular inhibitors as well as immune checkpoint inhibitors for the management of locally advanced and metastatic disease. Methods: A comprehensive review of the literature was performed using the keywords "conjunctival melanoma", "immune checkpoint inhibitors", "BRAF inhibitors", "MEK inhibitors", "CTLA4 inhibitors", "PD1 inhibitors", "c-KIT mutations", "BRAF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 118 publications
(319 reference statements)
0
21
0
Order By: Relevance
“…The study showed positivity for BRAF V600E and Q61X NRAS mutations in 25% of the cases each, which is similar to the data described by Griewank et al (20) (29% and 20%). However, other publications, such as Kenawy et al (18) and Larsen et al (19) , identified BRAF V600E mutations in primary tumors with much higher numbers, 40.4% and 50%, respectively. Recently, Gkiala et al (17) have shown that in a literature review with 563 CMs, 29.7% (n=167) harbored BRAF mutations and only 6.4% (n=36) harbored NRAS mutations.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The study showed positivity for BRAF V600E and Q61X NRAS mutations in 25% of the cases each, which is similar to the data described by Griewank et al (20) (29% and 20%). However, other publications, such as Kenawy et al (18) and Larsen et al (19) , identified BRAF V600E mutations in primary tumors with much higher numbers, 40.4% and 50%, respectively. Recently, Gkiala et al (17) have shown that in a literature review with 563 CMs, 29.7% (n=167) harbored BRAF mutations and only 6.4% (n=36) harbored NRAS mutations.…”
Section: Discussionmentioning
confidence: 87%
“…No differences were found in terms of sex or age at presentation. However, CM with alterations in these markers has been occurring more frequently in young males (18,19) , although without statistical significance.…”
Section: Discussionmentioning
confidence: 92%
“…Conjunctival melanocytes are derived from the neural crest as uveal and cutaneous melanocytes, although they migrate in different waves (Hu et al, 2007; Iwamoto et al, 2002). Although more population studies are needed, current evidence suggests that the most common driver mutations in conjunctival melanoma are in the BRAF (~30%–70%), NF1 (~20%–30%), NRAS (~17%), and c‐KIT (~8%) genes that lead to constitutive activation of the MAPK pathway as well as mutations that result in activation of the PI3K/AKT/mTOR signaling pathway (Gkiala & Palioura, 2020).…”
Section: Diversity and Prevalence Of Driver Mutations In Melanoma Sub...mentioning
confidence: 99%
“…In recent decades, the incidence of conjunctival melanoma has been increasing similar to cutaneous melanoma, while the incidence of uveal melanoma has remained relatively stable. This is thought to be related to the result of environmental exposure to UV light (25)(26)(27). Conjunctival melanoma mostly arises from PAM (53-75%), but can also arise from conjunctival nevi (18-30%) or de novo (5%) (21,24).…”
Section: Ocular Surface Squamous Neoplasiamentioning
confidence: 99%